Pretreatment eosinophil counts as a predictive biomarker in non‐small cell lung cancer patients treated with immune checkpoint inhibitors - Eiji Takeuchi; Kensuke Kondo; Yoshio Okano; Seiya Ichihara; Michihiro Kunishige; Naoki Kadota; Hisanori Machida; Nobuo Hatakeyama; Keishi Naruse; Hirokazu Ogino; Hiroshi Nokihara; Tsutomu Shinohara; et al. (Thoracic Cancer, 2023)
Abstract Background The peripheral blood eosinophil count prior to treatment has potential as a predictive biomarker for a beneficial clinical response to cancer immunotherapies. Therefore, the present study investigated the impact of the eosinophil count on overall survival (OS) in non‐small cell lung cancer (NSCLC) patients treated with immune checkpoint inhibitors (ICI). Methods We retrospectively reviewed all patients diagnosed with NSCLC and treated with ICI monotherapy between March 2016 and August 2021 at National Hospital Organization Kochi Hospital and Tokushima University. Results A total of 166 patients were included. Fifty‐five patients had an eosinophil count of less than 100 cells/μL (Eo < 100). Nighty‐eight patients had an eosinophil count of 100 cells/μL or more, but less than 500 cells/μL (100 ≤ Eo < 500). Thirteen patients had an eosinophil count of 500 cells/μL or more (Eo ≥500). The median OS of all lung cancer patients was 476 days. The median OS of lung cancer patients with Eo <100, 100 ≤ Eo <500, and Eo ≥500 was 339, 667, and 143 days, respectively. A Kaplan–Meier univariate analysis showed a significant difference in OS between these three groups (p < 0.001). A Cox proportional regression analysis identified 100 ≤ Eo <500 (p = 0.04), ECOG PS score ≥ 2 (p = 0.02), tumor size ≥5 cm (p = 0.02), and PD‐L1 ≥ 1% (p = 0.01) as independent predictors of OS. Conclusion OS was significantly longer in ICI‐treated NSCLC patients with a pretreatment eosinophil count of 100 ≤ Eo <500 than in the other patients and, thus, has potential as a new predictive biomarker.